Chemoecology of Insect Eggs and Egg Deposition 2003
DOI: 10.1002/9780470760253.ch8
|View full text |Cite
|
Sign up to set email alerts
|

The Plant's Response towards Insect Egg Deposition

Abstract: Plant responses towards insect egg depositions range from changes in plant tissue to alterations of the plant's volatile bouquet. Such responses may result either in defence against herbivores or even in their protection. Defensive tissue changes in plants caused by egg depositions are known as formation of neoplasms and as hypersensitive response. Tissue changes that positively affect herbivores are induced by egg depositions of several gall forming insects. These manipulate plants to produce nutritive and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 99 publications
1
75
0
1
Order By: Relevance
“…For collecting volatiles from whole potted soybean plants, a six-arm-olfactometer was used as described by Turlings et al (2004 Soybean pods grow closely to the stem and thus did not fit into the volatile collection device used for single leaves. Therefore, volatiles emitted by soybean pods were sampled by solid phase microextraction (SPME).…”
Section: Volatile Samplingmentioning
confidence: 99%
“…For collecting volatiles from whole potted soybean plants, a six-arm-olfactometer was used as described by Turlings et al (2004 Soybean pods grow closely to the stem and thus did not fit into the volatile collection device used for single leaves. Therefore, volatiles emitted by soybean pods were sampled by solid phase microextraction (SPME).…”
Section: Volatile Samplingmentioning
confidence: 99%
“…However, for several systems it has been found that the emission of plant synomones can be induced by insect oviposition, and that these synomones will attract specific egg parasitoids (Meiners and Hilker, 1997;Meiners and Hilker, 2000;Hilker and Meiners, 2002;Hilker et al, 2002a;Colazza et al, 2004a;Colazza et al, 2004b;Fatouros et al, 2005;Fatouros et al, 2007;Fatouros et al, 2008;Fatouros et al, 2009). From an evolutionary point of view, both symbionts will take advantage of this 'early alert' (sensu Hilker and Meiners, 2006) mechanism, as the egg parasitoids would use such highly detectable and reliable volatiles induced in plants soon after herbivore eggs are laid, whereas the plants would increase their fitness by recruiting natural enemies of the herbivore eggs before significant damage has occurred, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying synomone emission are associated with the presence of plant damage, either during oviposition or as a consequence of unrelated feeding behaviour on the host plant, in combination with elicitors contained in the reproductive system secretion and/or in the saliva of the herbivore (Hilker et al, 2002a;Hilker et al, 2002b; Rodriguezsurface, both locally and systemically, that arrest the egg parasitoids Trichogramma brassicae Bezdenko and T. evanescens Westwood (Hymenoptera: Trichogrammatidae) (Fatouros et al, 2005;Fatouros et al, 2007). Similarly, Brussels sprout plants induced by singly laid eggs of P. rapae L. (Lepidoptera: Pieridae) arrest T. brassicae wasps (Fatouros et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female parasitoid foraging behaviour has been divided into a series of hierarchical steps: habitat preference, host community location, host location, host recognition and acceptance, and among the different ecological and physiological factors involved, chemical cues influence all of these steps (Vet & Dicke, 1992;Vinson, 1998;Steidle & van Loon, 2002). When dealing with host -egg parasitoid associations, stimuli indirectly associated with the presence of the host (Nordlund, 1994;Schmidt, 1994;Vinson, 1998;Powell, 1999) and coming from the planthost complex (Hilker & Mainers, 2002;Hilker et al, 2002) play a fundamental role.…”
Section: Introductionmentioning
confidence: 99%